Revisit intention ke gunung Bromo: Menguji peran destination image dan destination personality melalui mediasi place attachment: Revisit intention to Mount Bromo: Testing the role of destination image and destination personality through the mediation of place attachment - Akhrani, Lusy Asa; Mehdiviky, Muh. Mughny; Wulansari, Aryanti; Banjarnahor, Reinhard Alex Sandro; Sasmitha, Alivia Arkana; Susanto, Amin Heri (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Tourists are drawn to return to Mount Bromo by their memories and experiences while visiting. Because of its many unique qualities, Bromo is fascinating to explore in relation to revisiting intention through the lens of destination image, destination Personality, and place attachment. Through destination Personality, destination image, and place connection, the study aims to explore the determinants influencing revisit intention. Purposive sampling was utilized to successfully gather 553 respondents, subject to the condition that domestic tourists are at least eighteen years old and have visited Bromo at least three times. Path analysis was used in the research analysis, and the (α=0,938), destination image (α=0,89), Place Attachment Index (α=0,928), and revisit intention scale (α=0,97) were used for measurement. The study's findings point to a relationship between place attachment, destination Personality, and destination image that directly and indirectly influences domestic travellers' revisit intention to Mount Bromo. The growth and administration of Mount Bromo can benefit from the study's contribution. The manager's job is crucial if you want visitors who have already been to express interest in returning.